Novel Method for 5G Systems NLOS Channels Parameter Estimation - Vladeta Milenkovic; Stefan Panic; Dragan Denic; Dragan Radenkovic (International Journal of Antennas and Propagation)
For the development of new 5G systems to operate in mm bands, there is a need for accurate radio propagation modelling at these bands. In this paper novel approach for NLOS channels parameter estimation will be presented. Estimation will be performed based on LCR performance measure, which will enable us to estimate propagation parameters in real time and to avoid weaknesses of ML and moment method estimation approaches.